Necrotising Fasciitis of lower anterior abdominal wall post lower segment ceaserian section - Makhdoomi, Mahmood A.; Haraga, Abdelhamid; Joseph, Moly; Habeeb, Yasser Al (International Surgery Journal, 2018)
Necrotising fasciitis is a rapidly progressive inflammatory infection of the fascia with secondary necrosis of the subcutaneous tissue. The speed of spread is directly proportional to the thickness of the subcutaneous layer. It moves along the fascial plane. We are presenting a case report of 27 years old Saudi female with status post Lower segment caesarian section of 10 days’ duration presented with bluish discoloration of the lower anterior abdominal wall around the surgical scar with necrotic patches and surrounding induration with foul smelling discharge from the one pocket within this area. She underwent successful simultaneous incision and wide debridement of gross necrotic tissues; together with evacuation of the pus followed by secondary closure. Both general and plastic surgical teams were involved. Patient made uneventful recovery and discharged home in good condition.